2013
DOI: 10.1161/circinterventions.112.000149
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcysteine for the Prevention of Renal Outcomes in Patients With Diabetes Mellitus Undergoing Coronary and Peripheral Vascular Angiography

Abstract: Acetylcysteine is a safe, inexpensive, and readily available antioxidant that has been proposed as a prophylactic intervention for contrast-induced acute kidney injury on top of optimal hydration. In this regard, several randomized trials were completed and reached inconsistent results. 8,9 Such studies are limited by low statistical power and most failed to meet quality standards, such as allocation concealment, blinding, and intention-to-treat analysis. Systematic reviews have found high heterogeneity across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Most recent RCTs or meta-analyses do not show a protective effect of NAc against PC-AKI following coronary or peripheral angiography [ 66 , 80 84 ]. NAc also failed to affect clinical outcome in coronary or peripheral angiography [ 85 ] or to have a protective effect in CT [ 86 , 87 ] or in patients with diabetes mellitus undergoing coronary or peripheral angiography [ 88 , 89 ]. Comparative studies with NAc combined with saline or sodium bicarbonate protocols did not show any additional effect of protective effect of NAc [ 61 , 90 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most recent RCTs or meta-analyses do not show a protective effect of NAc against PC-AKI following coronary or peripheral angiography [ 66 , 80 84 ]. NAc also failed to affect clinical outcome in coronary or peripheral angiography [ 85 ] or to have a protective effect in CT [ 86 , 87 ] or in patients with diabetes mellitus undergoing coronary or peripheral angiography [ 88 , 89 ]. Comparative studies with NAc combined with saline or sodium bicarbonate protocols did not show any additional effect of protective effect of NAc [ 61 , 90 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies were RCTs. Fifty-five studies 12, provided the process of random allocation concealment and sequence generation; 21 studies 17,21,22,24,25,27,29,30,33,37,38,41,43,44,46,48,59,60,63,67,68 mentioned blinding of personnel and subjects and 21 studies 17,21,22,24,25,27,29,30,33,37,38,41,43,44,46,48,59,60,63,67,68 mentioned blinding of outcome assessment. No study mentioned the existence of bias.…”
Section: Assessment Of Quality Of the Studiesmentioning
confidence: 99%
“…Clinical studies have shown diabetes mellitus as an independent risk factor for CIAKI 12 due to enhanced renal medullary hypoxia and impaired endothelium-derived vasorelaxation. Previous pre-clinical studies have used a functional CIAKI model by simulating endothelial dysfunction by pre-treating rats with L-NAME (nitric oxide synthase inhibitor) and indomethacin (prostaglandin inhibitor).…”
Section: Introductionmentioning
confidence: 99%